Clinical characteristics and quality of life of patients with coronary heart disease before revascularization - Yu.A. Borkhalenko; О.J. Zharinov; N.B. Іvaniuk; K.O. Mikhaliev; O.P. Nadorak; О.А. Еpanchintseva; B.М. Тоdurov (Кардіохірургія та інтервенційна кардіологія)
The aim – to compare the clinical characteristics and quality of life (QoL) of patients with stable coronary artery disease with and without left ventricular (LV) systolic dysfunction selected for revascularization under real clinical practice conditions. Materials and methods. The cross-sectional single-center retrospective study analyzed data from clinical, instrumental examination and assessment of QoL according to MLHFQ, SAQ and SF-36 questionnaires in 242 patients with coronary artery disease consecutively prepared for revascularization interventions. The results were compared in patients with low (n = 94) and preserved (n = 148) LV ejection fraction (EF). Results. Group of patients with coronary artery disease and preserved left ventricular ejection fraction was characterized by greater proportion of women (23.4 vs. 12.2 %) patients with peripheral vascular disease (63.8 vs. 27.0 %) and arterial hypertension II–III degrees (98.9 vs. 21.9 %). However, during coronary angiography no differences were observed regarding number of the affected coronary arteries in patients with and without left ventricular systolic dysfunction. According to several scales of SF-36 and SAQ questionnaires, changes of QoL in patients with coronary artery disease and preserved left ventricular ejection fraction were at least as pronounced as in patients with reduced LVEF. Conclusions. The results make possible to determine clinical characteristics and particularities of QoL in patients with stenosing coronary atherosclerosis and preserved LVEF. The necessity to improve QoL plays a key role in determining the need in coronary angiography and subsequent revascularization intervention in patients with coronary artery disease with preserved LVEF.